Evaluation of Selected Honey and One of Its Phenolic Constituent Eugenol against L1210 Lymphoid Leukemia - Jaganathan, Saravana Kumar (ScientificWorldJournal, 2014)
People affected with leukemia are on the rise and several strategies were employed to thwart this deadly disease. Recent decade of research focuses on phenolic constituents as a tool for combating various inflammatory, cancer, and cardiac diseases. Our research showed honey and its phenolic constituents as crusaders against cancer. In this work, we explored the antileukemic activity of selected honey and one of its phenolic constituent eugenol against L1210 leukemia animal model. Results of this experiment showed that the selected honey samples as well as eugenol after intraperitoneal injection could not increase the median survival time (MST) of animals. Further, there was only slight marginal increase in the %T/C values of honey and eugenol treated groups. The number of phenolics present in the honey may not be a prime factor to promote antileukemic effect since there was no difference in the MST of two different honeys tested. This study limits the use of selected honey and eugenol against leukemia animal model.